2008
DOI: 10.1002/jmv.21193
|View full text |Cite
|
Sign up to set email alerts
|

Sequence analysis of the capsid gene of Aichi viruses detected from Japan, Bangladesh, Thailand, and Vietnam

Abstract: Sequence analysis of the capsid gene of Aichi viruses was performed on 12 strains detected in Japan, Bangladesh, Thailand, and Vietnam during 2002-2005. The phylogenetic tree constructed from 17 nucleotide sequences of the capsid gene of the strains studied and reference strains demonstrated that Aichi virus strains clustered into two branches. A classification of Aichi viruses based on the capsid gene was proposed, in which lineage I consists of the Aichi virus strains detected from Japan, Thailand, Vietnam, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
26
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 19 publications
4
26
0
Order By: Relevance
“…Previous studies demonstrated a high consistency between AiV genotypes determined based on the 3CD junction region and capsid gene (6,8), which is supported by a fact reported by another previous study that no phylogenetic evidence of recombination was detected between AiV genotypes A and B in any part of the genome (28). These previous findings strongly suggest that AiV genotypes determined by our genotypespecific RT-qPCR assay based on the VP0 region are consistent with those determined by the conventional genotyping method based on the 3CD junction region.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Previous studies demonstrated a high consistency between AiV genotypes determined based on the 3CD junction region and capsid gene (6,8), which is supported by a fact reported by another previous study that no phylogenetic evidence of recombination was detected between AiV genotypes A and B in any part of the genome (28). These previous findings strongly suggest that AiV genotypes determined by our genotypespecific RT-qPCR assay based on the VP0 region are consistent with those determined by the conventional genotyping method based on the 3CD junction region.…”
Section: Discussionmentioning
confidence: 92%
“…AiV was first identified as a new cytopathic virus in BS-C-1 cells (4), and virus isolation using BS-C-1 or Vero cells (4, 7), the enzyme-linked immunosorbent assay (ELISA) (3), and conventional RT-PCR (6,24,27) have since been used to identify AiVs in clinical stool specimens. Isolation of AiVs by cell culture is timeconsuming (about 4 to 6 weeks) (3), and both virus isolation and ELISA are less sensitive than conventional RT-PCR (24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on 3C and 3D (3CD) junction region nucleotide sequences, AiVs are currently classified into three genetically distinct genotypes (A to C) (2,25). They have been identified in Asian (14,15,23,26,27), European (2,7,12,13,16,17), South American (13), and African (19,20) countries, suggesting their worldwide distribution. Seroprevalence studies performed in several countries demonstrated a high percentage (80 to 99%) of AiV antibodies in adults (3,13,18,21,24), indicating widespread human exposure.…”
mentioning
confidence: 99%
“…Seroprevalence studies conducted in Japan and Europe suggest that infections with this agent are quite frequent (16,26). In the Western hemisphere, Aichi virus has been described only in Brazil, in clinical samples (7,14,16,17,19,22,24,25,27). In Venezuela, it is unknown whether Aichi viruses circulate in the population, and their eventual associations with diarrheal cases or sporadic outbreaks have not been documented.…”
mentioning
confidence: 99%